Bargaining risk governance within the context of China’s belt and road initiative: Perspectives derived from the Kindleberger Trap theory - Zhifeng Shen; Yongming Ye; Ahsan Siraj; Zhihui Li (PLoS ONE, 2025)
“Belt and Road” infrastructure projects frequently encounter bargaining risks. This study aims to explore the causes of bargaining behavior and investigate how to control bargaining behavior in projects. The study identifies the factors affecting bargaining risk and employs evolutionary game theory to examine the strategic decisions of Chinese contractors and host governments. The results show that lower negotiation and bargaining costs promote sustained cooperation in the negotiation process. When the value of the contract is substantial and the contractor receives less benefit from the contract than it claims from the host government, terminating the project is good for the contractor.